The power of the Buckley and Casson thesis: the ability to manage institutional idiosyncrasies - Henisz, Witold J (Journal of International Business Studies, 2003)
Recent patterns of rapid internationalization in sectors characterized by strong public interest and both government and domestic capital constraints seem, at first, inconsistent with the drivers of internationalization identified by Buckley and Casson (1976) for manufacturing industries in the postwar era. A more microanalytic perspective, however, identifies the ability to manage institutional idiosyncrasies as a firm-level capability akin to research or advertising that can drive internalization across national borders and thereby internationalization. These arguments are examined using evidence from the independent power production sector.